Oral corrective feedback in EFL/ESL classrooms: Classification models - Pham, Thi Hanh (H. : ĐHQGHN, 2018)
Corrective feedback in general, and oral corrective feedback (OCF) in particular, has been of interest to both language teachers and researchers in second language acquisition (SLA). Teachers focus more on positive feedback and concern if corrective feedback should be provided, and when and how to provide it (Ellis, 2017). By comparison, SLA researchers pay attention to negative feedback and its effectiveness. Having received great interest, there have been a number of attempts in defning and classifying OCF up to date. Different models of classifcation have been proposed with different aspects of OCF taken into consideration, namely implicitness/explicitness and input-providing and output-prompting. This paper aims to review a body of literature on OCF classifcation models in the feld of SLA.